SOLAR-PV BASED SINGLE INPUT MULTIPLE OUTPUT (SIMO) DC-DC CONVERTER FOR ELECTRIC VEHICLE APPLICATION - ABDUL SAMAD, NUR IZZATI (Universiti Teknologi PETRONAS, 2017)
Electric vehicles and hybrid electric vehicles are seen as the future of the automotive industry with its aim to replace the conventional combustion engine vehicle. This is due to its benefaction in reducing greenhouse gases, the main contributor to rising temperature of the earth. The use of clean and renewable energy efficiently in these vehicles not only helps battling climate change problems that the current generation is facing but also reduces the use of our diminishing natural resources. A DC-DC converter is a type of electric power converter that is used in an electric or hybrid electric vehicle to convert one level of voltage to another for the use of the vehicle’s system.